Management of Drug Induced Gingival Overgrowth (Digo) in a Patient with Cerebral Palsy Type Spastic Quadriplegia: A Case Report - Sari, Anggun Tri; Sylvyana, Melita; Yazid Yusuf, Harmas (Poltekkes Kemenkes Palu, 2024)
Drug Induced Gingival Overgrowth (DIGO) can be defined as local or general enlargement of the gingival tissue that occurs as a side effect of certain drugs such as immunosuppressive drugs, anticonvulsants and calcium channel blockers. Epilepsy is known to be closely related to cerebral palsy; 15-60% of children with cerebral palsy report having epilepsy requiring anticonvulsant drugs as routine therapy. When gingival enlargement occurs, it interferes with normal oral hygiene practices and can interfere with masticatory function. Gingival hyperplasia can be treated by stopping or changing drugs. In more severe cases, surgical treatment is required. A 6 year old boy patient with a history of epilepsy and cerebral palsy came with complaints of lumps in the gums of the right and left lower jaw. The patient started taking epilepsy medication about 3 years after being diagnosed with epilepsy. After about 1.5 years of taking epilepsy drugs, the patient experienced enlargement of all of his maxillary and mandibular gingiva. The patient was consulted to the Oral and Maxillofacial Surgery Department of Hasan Sadikin General Hospital, on intra-oral examination we found there was gingival enlargement that covered almost the entire tooth surface, the treatment plan was carried out by a surgical procedure in stages under general anesthesia. The results obtained after surgery showed that the shape of the gingiva was normal and the patient's masticatory function had improved. In cases where there is overgrowth of the gingiva to cover the entire tooth surface, surgical procedure is a standard procedure to restore the normal shape of the gingiva.